Pirólise térmica e catalítica de polímeros pós-consumo sobre catalisadores tipo AIMCM-4 - Santos, Tiago Gomes dos (2015)
Due to the increase in the production of post-consumer plastic waste, the improper disposal and long-term degradation of this material, Brazil has faced serious environmental impacts. In order to avoid a worsening situation, the catalytic pyrolysis has become a very attractive process within the chemical treatment of post-consumer polymers, reducing the operating limitations of thermal pyrolysis, thus promoting processes with lower energy expenditure and selectively generating product high added value. Thus, in the present work were synthesized by hydrothermal method, a series of acids with heterogeneous catalysts mesoporous AlMCM-48 type cubic structure containing different ratios of Si/Al (50, 100, 150) for application to the pyrolysis reaction. The syntheses were performed over a period of three days with the pH between 11-13 and a highly polymerized silica source, ie, the ratio CTMABr/TEOS 0.59. The catalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), thermal analysis via TG/DTG and nitrogen adsorption. Through these characterization techniques it was observed that it was possible to develop a series of catalysts with high cubic mesoporous ordering equivalent and thermally stable thermogravimetric profile, surface area and size relatively high pore volume and had agglomerated spherical morphology. The thermal and catalytic pyrolysis reactions were performed using high density polyethylene (HDPE) and polypropylene (PP), where a comparative analysis of the thermal and catalytic pyrolysis catalysts on different AlMCM-48 type was performed. Through the conversion curves it was possible to observe and compare the operating conditions to obtain a given conversion as a function of the temperature correlated with the results obtained by kinetic Isoconversional methods proposed by Flynn-Wall-Ozawa (FWO) and Vyazovkin, may analyze the influence of AlMCM-48 on the activation energy (Ea) of pyrolysis reactions. The results showed a remarkable effect of the catalyst to accelerate the process of pyrolysis. In the catalytic pyrolysis of HDPE that the catalyst was more efficiently presented the Si/Al = 50 ratio, with a yield of 77.31 %, and the PP to the most efficient catalyst was the Si/Al = 100 ratio, who presented a yield of 75.84 %. As for the kinetics, both methods have been effective isoconversão to determine Ea HDPE and PP. The method Vyazovkin exhibited lower activation energies, an average difference 87.220 kJ.mol-1 for HDPE and 111.811 kJ.mol-1 to PP compared with the FWO method. The Ea determined by both methods showed the same behavior on the dependence of conversion and Ea(HDPE) < Ea(PP). In this work, efficient kinetic results were obtained, compared to pyrolysis reactions involving the HDPE and PP over AlMCM-48 catalysts, providing a basis for the potential benefit of the chemical recycling of post-consumer polymers, potentially leading to an efficient process in terms of energy costs.